From Decision to Outcome: Determinants and Post-M&A Performance in Swedish Public Firms - Moilanen,Matias; Paldanius,Eetu (2025)
Purpose: This study aims to identify the firm-specific, industry, and macroeconomic factors that drive M&A activity among Swedish public companies, and to assess whether these acquisitions result in enhanced financial and operational performance in the subsequent years. Methodology: The study uses binary logistic regression to examine how firms, industry, and macroeconomic characteristics influence the likelihood of M&A activity. Post-acquisition performance is assessed through propensity score matching and subsequent OLS regressions that track changes in profitability, revenue, and efficiency over a three-year timeframe. Theoretical perspectives: The paper draws on agency theory, the resource-based view, and capital structure theories to explain M&A behavior and guide the selection of financial, strategic, and ownership variables used to analyze acquisition likelihood and post-M&A performance. Empirical foundation: The foundation of the study is a panel dataset of 1,019 Swedish public firms, including 554 acquirers and 465 non-acquirers, observed between 2015 and 2023. The dataset covers 11 sectors and combines firm-level financials with information on M&A activity. Conclusion: The study finds that firm size, asset efficiency, and intangible intensity significantly influence M&A activity, while leverage acts as a limiting factor. Although M&A does not appear to improve profitability in the short term, acquiring firms show strong revenue growth and delayed improvements in operational margins, suggesting long-term strategic gains. Moreover, asset efficiency is found to decline following acquisitions.